2003
DOI: 10.1002/jso.10255
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal mesothelioma treated by induction chemotherapy, cytoreductive surgery, and intraperitoneal hyperthermic perfusion

Abstract: This therapeutic strategy proved feasible and was well tolerated. Early results seem promising and consistent with a potentially major impact on survival in selected patients with PM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
9
1

Relationship

7
3

Authors

Journals

citations
Cited by 83 publications
(50 citation statements)
references
References 30 publications
2
46
0
Order By: Relevance
“…The 1-, 3-and 5-year survival varied from 60% to 88%, 43% to 65%, and 29 to 59%, respectively [4]. The results of our study parallel the findings of this review and previously published studies [10,[18][19][20][21][22][23][24]. We have generally adopted the similar treatment approach using CRS and perioperative intraperitoneal chemotherapy.…”
Section: Discussionsupporting
confidence: 92%
“…The 1-, 3-and 5-year survival varied from 60% to 88%, 43% to 65%, and 29 to 59%, respectively [4]. The results of our study parallel the findings of this review and previously published studies [10,[18][19][20][21][22][23][24]. We have generally adopted the similar treatment approach using CRS and perioperative intraperitoneal chemotherapy.…”
Section: Discussionsupporting
confidence: 92%
“…In well differentiated disease, surgical extirpation prolonged median survival time up to 229 months. These results are consistent with smaller series that have previously shown that surgery, whether debulking or radical resection along with intra-peritoneal chemotherapy significantly prolongs the median survival of patients [14,[39][40][41][42][43][44].…”
Section: Fig 2 Asupporting
confidence: 94%
“…The clinical results from the Milan NCI were published in a preliminary report of the first 20 cases [22] , a clinicopathological study [23] , an extensive prognostic analysis of potential clinical, pathological and biological variables [24] , and an assessment of the pattern of failure [25] . Forty-nine patients with DMPM were enrolled to test the association between potential prognostic variables and survival by multivariate statistical analysi [24] .…”
Section: Clinical Resultsmentioning
confidence: 99%